2005
DOI: 10.1007/bf03396721
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Innovation, Exploitative Innovation, and Ambidexterity: The Impact of Environmental and Organizational Antecedents

Abstract: Organizational ambidexterity (i.e., the ability to pursue exploratory and exploitative innovation simultaneously) is crucial to firm survival. In this study we explore how multiunit firms might develop ambidextrous organizational units in response to environmental demands. We examine how environmental and organizational antecedents affect a unit's level of organizational ambidexterity. Our study reveals that multiunit firms develop ambidextrous organizational units to compete in dynamically competitive environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
293
3
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(321 citation statements)
references
References 52 publications
14
293
3
11
Order By: Relevance
“…There is a very strongly and positively correlation among dimensions of ambidexterity and ambidexterity, and also among dimensions of contradictory organizational characteristics. These findings support results of previous studies (Gibson, and Birkinshaw, 2004;Jansen et al, 2005). Further, decentralization, formalization, and their interaction (contradictory organizational characteristics) are significantly and positively related to exploitation, exploration and their interaction (ambidexterity).…”
Section: Analysis and Test Of The Hypothesissupporting
confidence: 91%
See 1 more Smart Citation
“…There is a very strongly and positively correlation among dimensions of ambidexterity and ambidexterity, and also among dimensions of contradictory organizational characteristics. These findings support results of previous studies (Gibson, and Birkinshaw, 2004;Jansen et al, 2005). Further, decentralization, formalization, and their interaction (contradictory organizational characteristics) are significantly and positively related to exploitation, exploration and their interaction (ambidexterity).…”
Section: Analysis and Test Of The Hypothesissupporting
confidence: 91%
“…Furthermore, interaction between decentralization and formalization positively influences an organization to pursue exploratory and exploitative simultaneously (R 2 = .153). These findings contribute to recent research proposing that organizations become more ambidextrous by combining contradictory elements (Adler and Borsy, 1996;Gibson, and Birkinshaw, 2004;Jansen et al, 2005). Also, interaction of formalization and connectedness affects organizational ambidexterity in a positive way.…”
Section: Analysis and Test Of The Hypothesissupporting
confidence: 78%
“…O'Reilly and Tushman (2008) found that organizations applying exploration and exploitation strategy usually survive. Their fi ndings support Jansen et al, (2005) who stated that exploration and exploitation concepts are very important for organization as they are being called ambidextrous. Ambidextrous organizations bear emphasis on the following issues (Raisch et al, 2009): Diff erentiation and integration, as separate 1.…”
Section: Introductionsupporting
confidence: 61%
“…Por fim, a abordagem do balanceamento temporal, como o próprio nome sugere, trata-se de uma separação temporal entre fases de exploration e exploitation, que pode partir de demandas externas, fatores situacionais, ou mesmo de acordo com a estratégia da organização (JANSEN et al, 2005). Ainda segundo o autor, o comportamento das organizações conforme explicado acima pode ser considerado dinâmico, no entanto, as organizações podem apresentar uma configuração estática com o passar do tempo, com pré-definições das proporções de atividades e projetos dedicados exploration e exploitation, por exemplo.…”
Section: Ambidestria Organizacional: Conceitos E Definiçõesunclassified